Physical therapists practice forms in sports first aid: a brazilian literature review - Suelena Ponte da Silva; Stela Lopes Soares; Paulo Adriano Schwingel (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2019)
First aid is the care provided to victims of any accident or sudden injury before the arrival of the doctor, ambulance or any qualified health professional. The objective of this study is to identify the physiotherapist's way of acting in first aid in sport. This is a bibliographic review, in which 2 books and 8 scientific articles obtained in the databases LILACS, MEDLINE and SciELO were used from January to March 2018. The results showed that the physiotherapist will act in the sports first aid by means of the PRICE method. However, it is necessary to carry out new studies that emphasize this topic, so that we can have a greater theoretical contribution. The majority of the analyzed studies reported the role of physiotherapy more oriented to preventive measures and rehabilitation.